Restful Web Service Sistem Presensi Mahasiswa (Studi Kasus Fakultas Teknologi Informasi dan Komunikasi Universitas Semarang) - DEWI NURDIYAH; Sri Handayani (Jurnal Transformatika, 2018)
The Student attendance at the Faculty of Information Technology and Communication University of Semarang  is data that can support in academic activities. validity and realbility of the attendance data  become obstacles in academic activities. So, Required attendance system that can prevent the occurrence of cheating attendance, facilitate lecturers to recap student attendance and facilitate administrative staff to recap lecturers’s attendance. In this research, student attendance system is made with two platforms, there are web based platform and platform based on android. Restful web service with JSON format is used to build communication between both platforms. In the attendence system android based, QRCode's Reader is used to read student QRCode cards to save attendance data. student dan lecture attendance can be monitored through attendance system web based. The attendance system test is done by testing all of the features and complexity of the algorithm with cyclomatic complexity. The test results show that all features can be used without error and cyclomatic complexity value show that algorithm of the attendance system  is easy to understand, easy to test and easy to maintain.